The Effectiveness of Telenursing Dietary Change Program for Elderly with Dyslipidemia - Aramthong, Suphitcha; Sirisopon, Nutthakritta; Chirasatienpon, Tharisara (Journal of The Royal Thai Army Nurses, 2025)
This quasi-experimental study aimed to evaluate the effectiveness of telenursing dietary change program for elderly with dyslipidemia by assessing changes in intrapersonal factors based on Self-efficacy theory and dietary behaviors. The sample consisted of 60-69-year-old who had received services at the OPD Telemedicine of Bhumibol Adulyadej Hospital, Royal Thai Air Force, and had LDL-C levels exceeding 100 mg/dL. The sample size of 32 was determined using a statistical formula, and participants were equally divided into an experimental group and a comparison, with 16 in each group, selected through simple random sampling. The experimental group received a telenursing dietary change program for four weeks, while the comparison group received standard telenursing care according to hospital protocols. Data were collected using a researcher-developed questionnaire and were analyzed using percentages, mean, and standard deviation, including Paired samples t-test for within-group comparisons and independent t-test for between-group comparisons. The results showed that the experimental group significantly increased perceived self-efficacy, outcome expectations, and dietary behavior compared to the pre-intervention period and the comparison group at a statistically significant level of .05. In conclusion, these findings suggest that the telenursing dietary change program was effective in improving the dietary behaviors of elderly individuals with dyslipidemia.